Dedikasi Melalui Kebugaran Jasmani Terhadap ABK Di SLB PRI Buaran Pekalongan - Imroatul Maghfiroh, Imroatul (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2022)
The purpose of this community service is dedication through physical fitness exercises that can be done every day for Children with Special Needs so that their physical fitness is well maintained. This community service was carried out at SLB PRI Buaran Pekalongan. The material presented at this seminar is about forms of physical fitness exercise that can be done every day for Children with Special Needs. The results of the implementation of community service are expected to give the spirit of Children with Special Needs where physical fitness must be maintained every day.